The Impact of Electronic Commerce on Economic Growth in The Kingdom of Saudi Arabia - Nasurlddin, Vivian Mohammed Saleh; Bokhari, Abla AbdulHameed; Alsilami, Tahani Masoud (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aimed at investigate the impact of e- commerce on economic growth in the Kingdom of Saudi Arabia, during the period 1995- 2020. For this purpose, a multiple linear regression analysis model was relied upon to express the relationship between economic growth and e- commerce related variables. The results showed high significance and a positive impact of the number of mobile phone subscriptions, the percentage of trade to GDP, and the number of shares traded via the Internet, on the GDP. Despite the statistical significance of the percentage of Internet users, ratio of mobile subscribers in the population, the number of transactions executed through the Internet, and ratio of communications and computers to service imports, their negative impact on economic growth in the Kingdom reflects the need to direct technology and its uses towards productive purposes. This indicates the importance of cooperation in spreading awareness and culture of purposeful use of information and communication technology in various business, daily commercial activities, and in e- commerce applications, as well as awareness of the importance of creating new investment opportunities based on innovation, which is the main driver of economic growth and an important tool for diversifying sources income.